25 Evaluation of a multi site specialist palliative care at home intervention. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Johnston, Bridget; Patterson, Anne; Wilson, Eleanor; Almack, Kathryn; Bird, Lydia; Mathews, Gillian; Seymour, Jane
Abstract : Background: The Midhurst Macmillan Specialist Palliative Care at Home Service was founded in 2006 to improve community-based palliative care provision. Principal components include; early referral; home-based clinical interventions; close partnership working; and flexible teamwork. Following a successful introduction, the model was implemented in six further sites across England. This article reports a mixed methods evaluation of the implementation across these 'Innovation Centres'. Aim: To assess the process and impact on staff, patients and carers of providing Macmillan Specialist Care at Home services across the six sites. Methods: A longitudinal, mixed methods research design. Data collection over 15 months (2014–2016) included: Quantitative outcome measures:- Palliative Performance Scale [PPS]; Palliative Prognostic Index [PPI] (n=2, 711); Integrated Palliative Outcome Scales [IPOS] (n=1, 157); Carers Support Needs Assessment Tool [CSNAT] (n=241); Views of Informal Carers – Evaluation of Services [VOICES-SF] (n=102); a custom-designed Service Data Tool [SDT] (n=88). Qualitative data methods:- focus groups with project team and staff (n=32 groups, [n=190 participants]), and, volunteers (n=6 groups, [n=32 participants]). Quantitative data analysis – SPPS vs 21; Qualitative data – thematic analysis. Results: Comparison across the different sites revealed contrasting modes of implementation. PPS, PPI and IPOS data exposed disparity in early referral criteria, complicated by conflicting interpretations of palliative care. The qualitative analysis, CSNAT and VOICES-SF data confirmed the value of the Macmillan model of care but uptake of the specialist home-based clinical intervention component was limited. Significant findings included better co-ordination of palliative care through project management and a single referral point and multi-disciplinary teamwork including leadership from consultants in palliative medicine, the role of health care assistants in rapid referral, and volunteer support. Discussion: Specialist palliative care teams enhance the quality of palliative and end of life care in the community setting and should form an integral part of future policy in this area.